PENINGKATAN VISIBILITAS BANGUNAN LAMA, STUDI KASUS JALAN KREMBANGAN BARAT SURABAYA - Setyo Nugroho (Lembaga Penelitian dan Pengabdian pada Masyarakat (LPPM) Universitas Kristen Duta Wacana Yogyakarta, 2015)
Title: The Improvement of Old Building Visibility, Krembangan Barat Street of Surabaya as of Case Study High development in the City center forces old building losing its existence. The main factor old buildings losing its existences are the lack of skyline guideline (new buildings obstruct the view toward old buildings), the changes of traffic direction, and the selection of vegetation type. This paper discusses a brief evaluation of old building visibility through visual experiences, and gives a schematic design as proposal for jalan Krembangan Barat. Serial vision technique analysis is addressed in order to gain the visual and spatial experiences of the built environment. Result shows that three spots of place should be improved in order to perceive the visibility by rehabilitating, adaptive re-using, and providing pedestrian ways to connect one potential spot to others in the corridor of Krembangan Barat.